EGEA Collection: A Biobank Devoted to Asthma and Asthma-related Phenotypes. (4th April 2017) - Nadif, Rachel; Bouzigon, Emmanuelle; Le Moual, Nicole; Siroux, Valérie
The Epidemiological study on the Genetics and Environment of Asthma (EGEA) is a 20-year cohort including cases with asthma (n = 388), their first degree relatives (n = 1244) and population-based controls (n = 415) recruited in the early 90's from five French cities. Participants were extensively characterized regarding environment and respiratory health, and a specific effort was made to trace and bank biological samples (ISO 9001 certification since 2006). Access to data and samples is opened to researchers wishing to develop new scientific collaborative programs. The survey has already led to more than a hundred papers with almost one third in collaboration with national and international teams.